Investigation of the relationship between ionospheric foF2 and earthquakes - Karaboga, Tuba; Canyilmaz, Murat; Ozcan, Osman (Elsevier Sci Ltd, 2018)
Variations of the ionospheric F2 region critical frequency (foF2) have been investigated statistically before earthquakes during 1980-2008 periods in Japan area. Ionosonde data was taken from Kokubunji station which is in the earthquake preparation zone for all earthquakes. Standard Deviations and Inter-Quartile Range methods are applied to the foF2 data. It is observed that there are anomalous variations in foF2 before earthquakes. These variations can be regarded as ionospheric precursors and may be used for earthquake prediction. (C) 2018 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Critical frequency; Earthquake; Earthquake prediction; Ionospheric precursors